Two new species of Tenomerga Neboiss from eastern Asia (Coleoptera: Cupedidae) - Wang, Cheng-Bin; Hájek, Jiří (Zootaxa, 2018)
Two new species of reticulated beetles (Cupedidae) are described: Tenomerga angulinota sp. nov. from Laos and T. helii sp. nov. from Sichuan, China. Important morphological characters of both new species are illustrated. T. angulinota sp. nov. can be easily recognized from all other Palaearctic-Oriental species by bifid anterior angles of pronotum; T. helii sp. nov. is in habitus very similar to widespread T. anguliscutis (Kolbe, 1886) and can be distinguished based on shape of pronotum, colour pattern of elytra and predominantly male genitalia. In addition, T. anguliscutis is for the first time recorded from Hainan and Jiangxi Provinces of China.